Konsep Islamic Parenting Menurut Pemikiran Aisah Dahlan dalam Buku Maukah Jadi Orang Tua Bahagia” Program Magister Pendidikan Agama Islam - Sulastri Sulastri; Hifza Hifza; Ahmad Zabidi (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is based on technological advancements that are in line with everyday life and children grow up in line with rapidly developing technology, from television to computers, smartphones, mobile devices with advanced technology and various applications. Most of their time spent in digital technology, so there are concerns from parents about the negative impacts on children. The purpose of this study is 1) Understanding the basic foundation Aisah Dahlan's thoughts on Islamic parenting in the book Maukah Jadi Orang Tua Bahagia. 2) Analyzing Islamic parenting methods according to Aisah Dahlan's thoughts in the book Maukah Jadi Orang Tua Bahagia. 3) Analyzing Islamic parenting techniques according to Aisah Dahlan's thoughts in the book Maukah Jadi Orang Tua Bahagia. This study uses a descriptive qualitative approach with the type of Library Research or text study. In this study, the primary data source was taken from Aisah Dahlan's book on Islamic parenting,